PENGARUH PENAMBAHAN SIROP UMBI YAKON (Smallanthus sonchifolius) TERHADAP KANDUNGAN GIZI DAN TOTAL TRIPTOFAN DADIH SUSU SAPI - Balqis Salsabila, (2022)
Non-communicable diseases are the main causes of death worldwide, one of which is type 2 Diabetes Mellitus (DM). Cow's milk dadih with a hypoglycemic effect developed to prevent type 2 DM increased prevalence. This study aimed to analyze the effect of adding yacon tuber syrup to the nutritional content, total tryptophan, organoleptic properties and determine selected formula of cow's milk dadih. This study used a completely randomized design (CRD), one factor two repetitions. Nutritional content and total tryptophan were analyzed by ANOVA test continued with Duncan test. Organoleptic tests were analyzed by Kruskal Wallis test continued with Mann Whitney test. Selected formula determination used the method of exponential comparison (MPE). The results of the analysis showed that there was no effect of adding yakon tuber syrup to water, ash, protein, and fat content of cow's milk dadih (p>0.05), but it showed a significant effect on carbohydrate content (p<0.05). The results of the organoleptic test showed that there was no effect of adding yacon tuber syrup to the parameters of color, aroma, and texture of cow's milk dadih (p>0.05), but it showed a significant effect (p<0.05) on taste parameter. The selected formula is the F3 with 30% of the yacon tuber syrup proportion added.